(untitled) (Journal of Partial Differential Equations, 2020)
"This paper deals with non-autonomous fractional stochastic reaction-diffusion equations driven by multiplicative noise with s 2208 (0,1). We first present some00a0 conditions for estimating the boundedness of fractal dimension of a random invariant set. Then we establish the existence and uniqueness of tempered pullback random attractors. Finally, the finiteness of fractal dimension of the random attractors is proved."